SC

Tính bằng 2 cách

( 6/11 + 5/11 ) * 3/7

( 6/7 - 4/7 ) : 2/5

NM
4 tháng 5 2018 lúc 14:37

\(C1:\left(\frac{6}{11}+\frac{5}{11}\right).\frac{3}{7}=1.\frac{3}{7}=\frac{3}{7}\)

\(C2:\left(\frac{6}{11}+\frac{5}{11}\right).\frac{3}{7}=\frac{6}{11}.\frac{3}{7}+\frac{5}{11}.\frac{3}{7}=\frac{18}{77}+\frac{15}{77}=\frac{3}{7}\)

\(C1:\left(\frac{6}{7}-\frac{4}{7}\right):\frac{2}{5}=\frac{2}{7}:\frac{2}{5}=\frac{5}{7}\)

\(C2:\left(\frac{6}{7}-\frac{4}{7}\right):\frac{2}{5}=\frac{6}{7}:\frac{2}{5}-\frac{4}{7}:\frac{2}{5}=\frac{15}{7}-\frac{10}{7}=\frac{5}{7}\)

Bình luận (0)